The Generational Interest Differences in Cash Waqf Insurance - Patriana, Ela; Aisyah, Muniaty; Al Arif, Mohammad Nur Rianto (ETIKONOMI, 2025)
Research Originality: Cash waqf insurance is underexplored in Islamic finance, offering a unique lens for study. This research addresses the gap by examining how knowledge, perceived fairness, and perceived usefulness influence attitudes and behavioral intentions toward cash waqf insurance among Generation Z, Millennials, and Generation X.Research Objectives: The study aims to assess the impact of these factors on shaping attitudes and intentions toward cash waqf insurance. Integrating these factors into the Theory of Planned Behavior (TPB) optimizes public understanding and fosters positive engagement on cash waqf.Research Method: 437 data sets were collected from respondents across three generations and analyzed using Partial Least Squares- Structural Equation Modeling (PLS-SEM) and multi-group analysis (MGA). The study evaluates the direct effects of knowledge, perceived fairness, and perceived usefulness on attitudes, behavioral intentions, and generational differences in these relationships.Findings: Knowledge significantly affects attitudes for Gen Z and Millennials, but not Gen X. Perceived fairness strongly influences Gen X and Gen Z, but not Millennials. Perceived usefulness is a key factor across all generations, with the highest impact on Millennials.Implications: The findings highlight the need for targeted educational campaigns for younger generations and fairness-based strategies for older cohorts. Policymakers and institutions can use these insights to enhance engagement with cash waqf insurance products.JEL Classification: G22, Z12, C38How to Cite:Patriana, E., Aisyah, M., & Al Arif, M. N. R. (2025). The Generational Interest Differences in Cash Waqf Insurance. Etikonomi, 24(1), 299 – 314. https://doi.org/10.15408/etk.v24i1.41731.